Pengaruh Rasio Fundamental Terhadap Return Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia 2012-2014 - Sulistyono, Jefri, Zulfa Irawati, S.E., M.Si (2017)
This study aims to determine determine the effect of Fundamental Ratios On Return Shares In Manufacturing Company Registered in BEI. The data used in this study was 131 data. The sampling technique in this research is purposive sampling data analysis method used is the classic assumption test and multiple linear regression analysis test, t test, F test, and the coefficient of determination (R2). The findings indicate that either partially or Return On Asset, Devidend Yield, Net Profit Margin, Quick Ratio, and Return On Equity significant effect on stock returns while Current Ratio, Debt Equity Ratio, Total Asset Turnover,Earning Yield, Book to Market Ratio, and Working Capital to Total Asset no significant effect on stock returns. Simultaneously CR, DER, TATO, ROA, DY, EY, BMR, WCTA, NPM, QR, and ROE significant effect on stock returns. All independent variables in this study were able to explain the variable stock return of 51.6% and the remaining 48.4% is explained by other variables outside the test model of this study.